2017
DOI: 10.1016/j.chemolab.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Standardized maximim D -optimal designs for enzyme kinetic inhibition models

Abstract: Locally optimal designs for nonlinear models require a single set of nominal values for the unknown parameters. An alternative is the maximin approach that allows the user to specify a range of values for each parameter of interest. However, the maximin approach is difficult because we first have to determine the locally optimal design for each set of nominal values before maximin types of optimal designs can be found via a nested optimization process. We show that particle swarm optimization (PSO) techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Further, as P.-Y. Chen et al (2017) showed, their speed and ability to provide approximate solutions to the optimum can also lead to an informed conjecture of the global solution that can enable an analytical derivation of the global optimum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, as P.-Y. Chen et al (2017) showed, their speed and ability to provide approximate solutions to the optimum can also lead to an informed conjecture of the global solution that can enable an analytical derivation of the global optimum.…”
Section: Discussionmentioning
confidence: 99%
“…In P.-Y Chen et al (2017),. the parameter space of (km, kic) was set as [4, 5] Â [2, 3], and the design space was [15, 30] Â[30, 60].…”
mentioning
confidence: 99%
“…They are difficult to find because we have a nested bi-level optimization problem and techniques to search for them are beyond the scope of this paper. Some recent work in constructing minimax or maximin approach using various techniques for different types of design problems are Duarte et al (2018) and Chen et al (2015, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further possibilities regarding the optimization process are robust criteria for design of experiments which are less sensitive to the initial values used for parameter estimation, e.g., the maximin design for optimizing the worst possible performance of any value θ in the parameter space (Körkel et al, 2004; Chen et al, 2017; van Daele et al, 2017; Telen et al, 2018).…”
Section: Michaelis-menten Kinetics As An Example In the Context Of Momentioning
confidence: 99%